Application of demographic analysis for assessing effects of pesticides on the predatory mite, Phytoseiulus persimilis (Acari: Phytoseiidae) - Mahmoud Monir Ahmed; Hala Rashad Abdel-Rahman; Mohammed Ali Abdelwines (Persian Journal of Acarology)
Knowing pesticides' side-effects on non-target beneficial phytoseiids is crucial for integrated mite management (IMM) programs. The present study investigates the sublethal effects of three fungicides: previcur N (Propamocarb-Hydrochloride 72.2%), penazol 10% EC (Penconazol) and sumi-eight 5% EC (Diniconazole); two insecticides: confidor 20% SL (Imidacloprid) and penny 9% SC (Emamectin benzoate 1.5% & Indoxacarb 7.5%), and two common acaricides: agnar (Spirodiclofen 18% + Abamectin 2%) and biomectin 5% EC (Abamectin) on the predatory mite, Phytoseiulus persimilis Athias-Henriot under both laboratory and greenhouse conditions. The toxicity bioassay and greenhouse experiments revealed that the effects of agnar, confidor and previcur N on P. persimilis is less than other compounds. Therefore, they were selected to evaluate their influence on the population parameters of P. persimilis. Based on the age-stage two-sex life table theory, the LC25 of tested pesticides significantly reduced the longevity, life span and total fecundity of female P. persimilis. Also, it reduced the net (R0) and gross (GRR) reproductive rates. Consequently, the intrinsic (r) and finite (λ) rates of increase were affected. In conclusion, the selected pesticides should not be used with P. persimilis in integrated pest management programs due to their unfavorable effects on the population parameters of this predatory mite.